Causal Effect of Blood Pressure on Bone Mineral Density and Fracture: A Mendelian Randomization Study - He, Bin; Yin, Lifeng; Zhang, Muzi; Lyu, Qiong; Quan, Zhengxue; Ou, Yunsheng (Frontiers in Endocrinology, 2021)
Background Hypertension may have some association with osteoporosis. This Mendelian randomization (MR) study aimed to explore the causal effect of blood pressure (BP) on bone mineral density (BMD), fall, and fracture. Methods We used the genome-wide association study (GWAS) summary data among 330,956 European-descent individuals to identify 107 single-nucleotide polymorphisms (SNPs) as the instrumental variables of BP. MR analyses of these instruments were performed on 53,236 European individuals for the association with forearm BMD (FA-BMD), femoral neck BMD (FN-BMD), and lumbar spine BMD (LS-BMD); 451,179 European individuals for fall susceptibility; and up to 1.2 million individuals from European descent for fracture. Conventional inverse variance weighted (IVW) method was adopted to obtain the causal estimates of BP on different outcomes, while weighted median, MR-egger, and MR pleiotropy residual sum and outlier (MR-PRESSO) test were used for sensitivity analyses. Results Genetically high pulse pressure (PP) could significantly improve FA-BMD (beta-estimate: 0.038, 95% confidence interval [CI]: 0.013 to 0.063, SE:0.013, P-value=0.003<Bonferroni correction P) in the IVW analysis, indicating that 1-SD increase in PP was associated with the improvement in FA-BMD levels by 0.038 g/cm2 (95% CI: 0.013 to 0.063). This positive finding was also confirmed by weighted-median analysis (beta-estimate: 0.034, 95% CI: 0.000 to 0.067, SE:0.017, P-value=0.046) and MR-Egger analysis (beta-estimate: 0.117, 95% CI: 0.026 to 0.208, SE:0.046, P-value=0.011). However, there was no remarkable MR association between BP and other outcomes (i.e., FN-BMD, LS-BMD, fall, and fracture). Conclusions Our findings reveal a potentially causal relationship between high PP and improved FA-BMD, which may provide new sights for the treatment of osteoporosis.